Hollow core-shell structured Si@NiAl-LDH composite as high-performance anode material in lithium-ion batteries. (20th January 2020) - Li, Qiongguang; Wang, Yanhong; Lu, Bin; Yu, Jing; Yuan, Menglei; Tan, Qiangqiang; Zhong, Ziyi; Su, Fabing
Abstract: Vast volume expansion of Si-based materials severely deteriorates the electrochemical performance of lithium-ion batteries (LIBs). To overcome this problem, we designed and synthesized Si@NiAl-LDH (layered double hydroxide) hybrid composites with the unique hollow core-shell structure via a re-precipitation and in situ growth process. In principle, the core of Si nanoparticles (Si NPs) can contribute to a high Li-storage capacity, the void space between the shell of LDH and the Si-core can effectively tolerate the volume expansion of Si NPs, and the shell can maintain the structural integrity and contribute to the electrochemical performance as well. As demonstrated, when used as the anode materials of LIBs, Si@NiAl-LDH exhibited much enhanced electrochemical performance as compared with the LDHs. The Si@NiAl-LDH electrode had a reversible capacity of 534 mAhg −1 after 60 cycles at 50 mAg −1 while that of NiAl-LDH was 343 mAhg −1 only. Regarding the rate performance, the Si@NiAl-LDH electrode could revert to 565 mAhg −1 after a rate test, while that of NiAl-LDH electrode was 353 mAhg −1 only. Obviously, the obtained clear structure-property relationship of the anode materials will be very conducive to the design and synthesis of the high-performance next-generation materials for energy storage and conversion. Highlights: Si@NiAl-LDH composite with Si-nanoparticle core and LDH shell is synthesized. Si@NiAl-LDH as anode material shows enhanced properties as compared with NiAl-LDH. The hollow core-shell structure buffers the volume expansion of Si. NiAl-LDH shell with a layered structure has a high surface area.